Menantang Kekuatan Partisipasi Siswa Meraih ''Petualangan Pengetahuan" dengan Pembelajaran Bercerita Menggunakan Kiasan dalam Al Qur’an - Isya', Muhammad Andi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Learning is an active process, students must participate or participate in the process of responses (responses) to the teacher's stimulus, so that students achieve optimal results. Student participation in learning is an absolute requirement to achieve the desired results. Building a structure for students to collect, analyze, and share data about the habit of reaching a "knowledge adventure" (for example, participation in class, persistence with revision) is an important part of creating a healthy learning culture and skills that will empower them to better understand patterns their personal behavior and learning Al-Qur'an The Qur'an is the main source in realizing the goal of Islamic education.This article aims to describe how Challenging the power of participation of students in achieving the "adventure of knowledge" with Learning to tell stories using figures of speech in the Qur'an. The results of the discussion can be summarized as follows: When idioms are used, figurative or symbolic language is used, it is not taken literally by evaluating what words ... that we cannot learn valuable insights about God, its values, its thinking, some principles behind historical narratives. Learning activities must be a "knowledge adventure" where students are challenged to participate in accordance with their own strengths, challenges and learning situations designed to make it to analyze and examine them, to find solutions that make sense of meeting. The teacher's role consists of more stimulating and guidance for students Motivation arises from the participation of enthusiastic teachers.Students who are involved in both teaching, learning and assessment, and discipline become self-discipline, ensured by cooperation satisfaction